Knowledge, attitude, and practices on occupational health and safety principles among cleaners: the case of Tikur Anbassa Specialized Referral Hospital, Addis Ababa, Ethiopia - Gebreeyessus Getachew Dagnew (Open Health, 2022)
This study was conducted to determine the occupational risks of cleaners of healthcare institutions like Tikur Anbassa Specialized Referral Hospital, Addis Ababa, Ethiopia. A cross-sectional study was conducted to assess the knowledge, attitude and practice of cleaners focusing on occupational health and safety issues, including biological and chemical risks. Interview data were collected using a structured questionnaire that involved all the cleaners. Additionally, focus group discussions and use of observational checklists were applied to capture both administrative and the actual waste management aspects. The result of the study showed that all cleaners had a favorable attitude towards safety principles. However, the knowledge of cleaners on occupational safety was so poor to the level that all of them did not even know the meaning of nosocomial infection. Almost all of the cleaners, 69 (98.6%), had not taken any preemployment training by the time of the interview. All of the cleaners’ practices were not fully compliant with the universal precaution principles and the major proportion, 37 (53%), of them had instances of needlestick injuries ranging from one to four times. Furthermore, the wastes in the hospital were located indiscriminately and with an uncovered container. Though cleaners had a desirable attitude, the status of occupational safety awareness and practice were not to the expected level that it should be. This institution, and similar institutions, should give emphasis to occupational safety issues with healthcare waste management. Awareness training has to be given before employment as well as refreshment trainings after engagement.